HW 5 Solution

HW 5 Solution - 228 4. Chapter 6. The Laplace Transform The...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 228 4. Chapter 6. The Laplace Transform The function f (t) has a jump discontinuity at t = 1. 7. Integration is a linear operation. It follows that A 0 cosh bt · e−st dt = = 1 2 A 0 1 2 A 0 ebt · e−st dt + 1 2 A 0 1 2 A 0 e−bt · e−st dt = e(b−s)t dt + e−(b+s)t dt . Hence 0 A cosh bt · e−st dt = 1 1 − e(b−s)A 1 1 − e−(b+s)A + . 2 s−b 2 s+b 1 1 1 s 1 + =2 . 2 s−b 2 s+b s − b2 Taking a limit, as A → ∞ , ∞ 0 cosh bt · e−st dt = Note that the above is valid for s > |b| . Sec 6.1, Pg 311 8. Proceeding as in Problem 7, A 0 sinh bt · e−st dt = 1 1 − e(b−s)A 1 1 − e−(b+s)A − . 2 s−b 2 s+b 1 1 1 b 1 − =2 . 2 s−b 2 s+b s − b2 Taking a limit, as A → ∞ , ∞ 0 sinh bt · e−st dt = The limit exists as long as s > |b| . 10. Observe that eat sinh bt = (e(a+b)t − e(a−b)t )/2 . It follows that A 0 eat sinh bt · e−st dt = 1 1 − e(a+b−s)A 1 1 − e−(b−a+s)A − . 2 s−a+b 2 s+b−a Taking a limit, as A → ∞ , ∞ 0 eat sinh bt · e−st dt = 1 1 1 1 b − = . 2 s−a+b 2 s+b−a (s − a)2 − b2 230 Taking a limit, as A → ∞ , ∞ 0 Chapter 6. The Laplace Transform teat · e−st dt = 1 . (s − a)2 Note that the limit exists as long as s > a . Sec 6.1, Pg 311 17. Observe that t cosh at = (t eat + t e−at )/2 . For any value of c , A 0 t ect · e−st dt = − t e(c−s)t s−c A A + 0 0 1 (c−s)t e dt = s−c = 1 − eA(c−s) + A(c − s)eA(c−s) . (s − c)2 ∞ 0 Taking a limit, as A → ∞ , tect · e−st dt = 1 . (s − c)2 Note that the limit exists as long as s > |c| . Therefore, ∞ 0 t cosh at · e−st dt = 1 1 1 + 2 (s − a)2 (s + a)2 = s2 + a2 . (s − a)2 (s + a)2 18. Integrating by parts, A 0 tn eat · e−st dt = − tn e(a−s)t s−a A A + 0 0 n n−1 (a−s)t t e dt = s−a =− An e−(s−a)A + s−a A 0 n n−1 (a−s)t t e dt . s−a Continuing to integrate by parts, it follows that A 0 tn eat · e−st dt = − − An e(a−s)A nAn−1 e(a−s)A − − s−a (s − a)2 n!Ae(a−s)A n!(e(a−s)A − 1) − ··· − . (n − 2)!(s − a)3 (s − a)n+1 n! , (s − a)n+1 That is, A 0 tn eat · e−st dt = pn (A) · e(a−s)A + in which pn (ξ ) is a polynomial of degree n . For any given polynomial, A→∞ lim pn (A) · e−(s−a)A = 0 , as long as s > a . Therefore, ∞ 0 tn eat · e−st dt = n! . (s − a)n+1 234 Chapter 6. The Laplace Transform Hence L−1 [Y (s)] = 3 + 5 cos 2t − 2 sin 2t . Sec 6.2, Pg 320 9. The denominator s2 + 4s + 5 is irreducible over the reals. Completing the 1 − 2s 5 − 2(s + 2) = . s2 + 4s + 5 (s + 2)2 + 1 We find that L−1 square, s2 + 4s + 5 = (s + 2)2 + 1 . Now convert the function to a rational function of the variable ξ = s + 2 . That is, ξ2 5 2ξ −2 = 5 sin t − 2 cos t . +1 ξ +1 Using the fact that L [eat f (t)] = L [f (t)]s→s−a , L−1 1 − 2s = e−2t (5 sin t − 2 cos t) . s2 + 4 s + 5 10. Note that the denominator s2 + 2s + 10 is irreducible over the reals. Completing the square, s2 + 2s + 10 = (s + 1)2 + 9 . Now convert the function to a rational function of the variable ξ = s + 1 . That is, 2s − 3 2(s + 1) − 5 = . s2 + 2s + 10 (s + 1)2 + 9 We find that L− 1 ξ2 2ξ 5 5 −2 = 2 cos 3t − sin 3t . +9 ξ +9 3 Using the fact that L [eat f (t)] = L [f (t)]s→s−a , L−1 2s − 3 5 = e−t (2 cos 3t − sin 3t) . s2 + 2s + 10 3 12. Taking the Laplace transform of the ODE, we obtain s2 Y (s) − s y (0) − y (0) + 3 [s Y (s) − y (0)] + 2 Y (s) = 0 . Applying the initial conditions, s2 Y (s) + 3s Y (s) + 2 Y (s) − s − 3 = 0 . Solving for Y (s), the transform of the solution is Y (s) = Using partial fractions, s+3 2 1 = − . s2 + 3 s + 2 s+1 s+2 Hence y (t) = L−1 [Y (s)] = 2 e−t − e−2t . 13. Taking the Laplace transform of the ODE, we obtain s2 Y (s) − s y (0) − y (0) − 2 [s Y (s) − y (0)] + 2 Y (s) = 0 . s+3 . s2 + 3 s + 2 234 Chapter 6. The Laplace Transform Hence L−1 [Y (s)] = 3 + 5 cos 2t − 2 sin 2t . 9. The denominator s2 + 4s + 5 is irreducible over the reals. Completing the square, s2 + 4s + 5 = (s + 2)2 + 1 . Now convert the function to a rational function of the variable ξ = s + 2 . That is, 1 − 2s 5 − 2(s + 2) = . s2 + 4s + 5 (s + 2)2 + 1 We find that L−1 ξ2 5 2ξ −2 = 5 sin t − 2 cos t . +1 ξ +1 Using the fact that L [eat f (t)] = L [f (t)]s→s−a , L−1 1 − 2s = e−2t (5 sin t − 2 cos t) . s2 + 4 s + 5 10. Note that the denominator s2 + 2s + 10 is irreducible over the reals. Completing the square, s2 + 2s + 10 = (s + 1)2 + 9 . Now convert the function to a rational function of the variable ξ = s + 1 . That is, 2s − 3 2(s + 1) − 5 = . s2 + 2s + 10 (s + 1)2 + 9 We find that L− 1 ξ2 2ξ 5 5 −2 = 2 cos 3t − sin 3t . +9 ξ +9 3 Using the fact that L [eat f (t)] = L [f (t)]s→s−a , L−1 2s − 3 5 = e−t (2 cos 3t − sin 3t) . s2 + 2s + 10 3 Sec 6.2, Pg 320 12. Taking the Laplace transform of the ODE, we obtain s2 Y (s) − s y (0) − y (0) + 3 [s Y (s) − y (0)] + 2 Y (s) = 0 . Applying the initial conditions, s2 Y (s) + 3s Y (s) + 2 Y (s) − s − 3 = 0 . Solving for Y (s), the transform of the solution is Y (s) = Using partial fractions, s+3 2 1 = − . s2 + 3 s + 2 s+1 s+2 Hence y (t) = L−1 [Y (s)] = 2 e−t − e−2t . 13. Taking the Laplace transform of the ODE, we obtain s2 Y (s) − s y (0) − y (0) − 2 [s Y (s) − y (0)] + 2 Y (s) = 0 . s+3 . s2 + 3 s + 2 248 Hence L−1 [F (ks)] = Chapter 6. The Laplace Transform 1 f k t k . 1 t (c) From part (b), L−1 [F (as)] = a f ( a ) Note that as + b = a(s + b/a). Using the ct fact that L [e f (t)] = L [f (t)]s→s−c , L−1 [F (as + b)] = e−bt/a 1 f a t a . 26. First write F (s) = n! . s ( 2 )n+1 Let G(s) = n!/sn+1 . Based on the results in Problem 25, 1 −1 s L G 2 2 in which g (t) = tn . Hence L−1 [F (s)] = 2 (2t)n = 2n+1 tn . = g (2t), 29. First write F ( s) = Now consider e−4(s−1/2) . 2(s − 1/2) e−2s . s 1 g 2 1 2 G(s) = Using the result in Problem 25(b), L−1 [G(2s)] = t 2 , 1 2 in which g (t) = u2 (t). Hence L−1 [G(2s)] = L−1 [F (s)] = u2 (t/2) = u4 (t). It follows that 1 t/2 e u4 (t). 2 30. By definition of the Laplace transform, ∞ L [ f (t)] = 0 e−st u1 (t)dt . 1 − e−s . s That is, 1 L [ f (t)] = 0 e−st dt = Sec 6.3, Pg 330 31. First write the function as f (t) = u0 (t) − u1 (t) + u2 (t) − u3 (t) . It follows that 1 L [ f (t)] = 0 e−st dt + 2 3 e−st dt . 6.3 That is, L [ f (t)] = 249 1 − e−s e−2s − e−3s 1 − e−s + e−2s − e−3s + = . s s s 32. The transform may be computed directly. On the other hand, using the translation property of the transform, 1 L [f (t)] = + s That is, L [f (t)] = 2n+1 k=1 1 e−ks = (−1) s s k 2n+1 (−e−s )k = k=0 1 1 − (−e−s )2n+2 . s 1 + e− s 1 − (e−2s )n+1 . s(1 + e−s ) 35. The given function is periodic, with T = 2 . Using the result of Problem 34, L [f (t)] = 1 1 − e−2s L [f (t)] = 2 0 e−st f (t)dt = 1 1 − e−2s 1 0 e−st dt . That is, 1 − e−s 1 = . s(1 − e−2s ) s(1 + e−s ) 37. The function is periodic, with T = 1 . Using the result of Problem 34, L [f (t)] = 1 1 − e−s 1 0 t e−st dt . It follows that L [f (t)] = 1 − e−s (1 + s) . s2 (1 − e−s ) 38. The function is periodic, with T = π . Using the result of Problem 34, L [f (t)] = 1 1 − e−πs π 0 sin t · e−st dt . 1 + e−πs . 1 + s2 We first calculate 0 π sin t · e−st dt = Hence L [f (t)] = 1 + e−πs . (1 − e−πs )(1 + s2 ) 6.3 That is, L [ f (t)] = 249 1 − e−s e−2s − e−3s 1 − e−s + e−2s − e−3s + = . s s s 32. The transform may be computed directly. On the other hand, using the translation property of the transform, 1 L [f (t)] = + s That is, L [f (t)] = 2n+1 k=1 1 e−ks = (−1) s s k 2n+1 (−e−s )k = k=0 1 1 − (−e−s )2n+2 . s 1 + e− s 1 − (e−2s )n+1 . s(1 + e−s ) 35. The given function is periodic, with T = 2 . Using the result of Problem 34, L [f (t)] = 1 1 − e−2s L [f (t)] = 2 0 e−st f (t)dt = 1 1 − e−2s 1 0 e−st dt . That is, 1 − e−s 1 = . s(1 − e−2s ) s(1 + e−s ) Sec 6.3, Pg 331 37. The function is periodic, with T = 1 . Using the result of Problem 34, L [f (t)] = 1 1 − e−s 1 0 t e−st dt . It follows that L [f (t)] = 1 − e−s (1 + s) . s2 (1 − e−s ) 38. The function is periodic, with T = π . Using the result of Problem 34, L [f (t)] = 1 1 − e−πs π 0 sin t · e−st dt . 1 + e−πs . 1 + s2 We first calculate 0 π sin t · e−st dt = Hence L [f (t)] = 1 + e−πs . (1 − e−πs )(1 + s2 ) 6.4 (b) 257 Due to initial conditions, the solution temporarily oscillates about y = 0 . After the forcing is applied, the response is a steady oscillation about ym = 1 . Sec 6.4, Pg 336 9.(a) Let g(t) be the forcing function on the right-hand-side. Taking the Laplace transform of both sides of the ODE, we obtain s2 Y (s) − s y (0) − y (0) + Y (s) = L [g (t)] . Applying the initial conditions, s2 Y (s) + Y (s) − 1 = L [g (t)] . The forcing function can be written as g (t) = with Laplace transform L [g (t)] = t t 1 [1 − u6 (t)] + 3 u6 (t) = − (t − 6)u6 (t) 2 22 1 e − 6s − . 2s2 2s2 Solving for the transform, Y (s) = Using partial fractions, 1 2s2 (s2 + 1) = 11 1 −2 . 2 2s s +1 s2 1 1 e−6s + 22 − 22 . +1 2s (s + 1) 2s (s + 1) Taking the inverse transform, and using Theorem 6.3.1, the solution of the IVP is y (t) = sin t + 1 1 [t − sin t] − [(t − 6) − sin(t − 6)] u6 (t) 2 2 1 1 = [t + sin t] − [(t − 6) − sin(t − 6)] u6 (t). 2 2 6.5 (b) 273 Sec 6.5, Pg 343 9.(a) Taking the initial conditions into consideration, the transform of the ODE is s2 Y (s) + Y (s) = Solving for the transform, Y ( s) = Using partial fractions, 3 e−(3π/2)s e−2πs e−(π/2)s + − . 2 + 1) 2+1 s( s s s(s2 + 1) 1 1 s = −2 . + 1) s s +1 e−(π/2)s e−2πs + 3 e−(3π/2)s − . s s s(s2 Hence s e−(π/2)s 3 e−(3π/2)s e−2πs s e−2πs e−(π/2)s − + − +2 . 2+1 2+1 s s s s s +1 Based on Theorem 6.3.1, the solution of the IVP is Y (s) = y (t) = uπ/2 (t) − cos(t − π 3π )uπ/2 (t) + 3 sin(t − )u3π/2 (t)− 2 2 − u2π (t) + cos(t − 2π )u2π (t) . That is, y (t) = [1 − sin(t)] uπ/2 (t) + 3 cos(t) u3π/2 (t) − [1 − cos(t)] u2π (t) . 286 Chapter 6. The Laplace Transform 3. It follows directly that t f ∗ f (t) = 0 sin(t − τ ) sin(τ ) dτ = 1 (sin t − t cos t). 2 = 1 2 t [cos(t − 2τ ) − cos(t)] dτ = 0 The range of the resulting function is R . Sec 6.6, Pg 350 5. We have L [e−t ] = 1/(s + 1) and L [sin t] = 1/(s2 + 1). Based on Theorem 6.6.1, t L 0 e−(t−τ ) sin(τ ) dτ = 1 1 1 ·2 = . s+1 s +1 (s + 1)(s2 + 1) 6. Let g (t) = t and h(t) = et . Then f (t) = g ∗ h (t) . Applying Theorem 6.6.1, t L 0 g (t − τ )h(τ ) dτ = 1 1 1 · =2 . s2 s − 1 s (s − 1) 7. We have f (t) = g ∗ h (t) , in which g (t) = sin t and h(t) = cos t . The transform of the convolution integral is t L 0 g (t − τ )h(τ ) dτ = 1 s s · =2 . s2 + 1 s2 + 1 (s + 1)2 9. It is easy to see that L− 1 1 = e−t s+1 and L−1 s2 s = cos 2t . +4 Applying Theorem 6.6.1, L−1 s = (s + 1)(s2 + 4) t 0 e−(t−τ ) cos 2τ dτ . 10. We first note that L− 1 1 = t e− t (s + 1)2 1 (s + 1)2 (s2 + 4) and L− 1 1 1 = sin 2t . s2 + 4 2 Based on the convolution theorem, L− 1 1 2 1 = 2 = t 0 t 0 (t − τ )e−(t−τ ) sin 2τ dτ τ e−τ sin(2t − 2τ ) dτ . 11. Let g (t) = L−1 [G(s)]. Since L−1 1/(s2 + 1) = sin t , the inverse transform of the product is L−1 G(s) = s2 + 1 t t g (t − τ ) sin τ dτ = 0 0 sin(t − τ ) g (τ ) dτ . 288 Chapter 6. The Laplace Transform Based on the elementary properties of the Laplace transform, L−1 1 4s2 + 4s + 17 t 0 = 1 −t/2 e sin 2t . 8 Applying the convolution theorem, the solution of the IVP is y (t) = 1 8 e−(t−τ )/2 sin 2(t − τ ) g (τ ) dτ . Sec 6.6, Pg 351 17. Taking the initial conditions into consideration, the transform of the ODE is s2 Y (s) − 2s + 3 + 4 [s Y (s) − 2] + 4 Y (s) = G(s). Solving for the transform of the solution, Y ( s) = We can write 2s + 5 G(s) + . (s + 2)2 (s + 2)2 2s + 5 2 1 = + . (s + 2)2 s + 2 (s + 2)2 2 = 2e−2t s+2 1 = t e − 2t . (s + 2)2 It follows that L− 1 and L−1 Based on the convolution theorem, the solution of the IVP is y (t) = 2e−2t + t e−2t + 0 t (t − τ )e−2(t−τ ) g (τ ) dτ . 19. The transform of the ODE (given the specified initial conditions) is s4 Y (s) − Y (s) = G(s). Solving for the transform of the solution, Y (s) = First write G(s) . s4 − 1 1 1 1 1 = −2 . s4 − 1 2 s2 − 1 s +1 L−1 It follows that 1 s4 − 1 t = 1 [sinh t − sin t] . 2 Based on the convolution theorem, the solution of the IVP is y (t) = 1 2 [sinh(t − τ ) − sin(t − τ )] g (τ ) dτ . 0 20. Taking the initial conditions into consideration, the transform of the ODE is s4 Y (s) − s3 + 5s2 Y (s) − 5s + 4 Y (s) = G(s). ...
View Full Document

Ask a homework question - tutors are online